APLIKASI PENGISIAN BAK AIR DAN KRAN OTOMATIS DENGAN MIKROKONTROLER - Ifni Joi; Tuti Anggraini (Elektron : Jurnal Ilmiah, 2013)
At the last project had made System to fill t the Automaticc reservoir. This equipment used electrode sensor level such as cuprum which use to detection the high water. Out put t his sensor will be proses by controller and controller give relay instruction to solenoid valve. If the water lack of the level, Controller will be active the valve antil the reservoir full, if the writer want the perfect equipment, the writer add the controller open close automatic valve. That worck is based on the distance of people to valve. If the distance of people near to valve, so the valve will open it self. As open loop controll system, valve use microcontroller AVR Atmega 8535 to Active the relay.